2014
DOI: 10.3906/fiz-1406-17
|View full text |Cite
|
Sign up to set email alerts
|

A study on Si and P doped h-BN sheets: DFT calculations

Abstract: Structural properties and energetics of silicon and phosphorus doped hexagonal boron nitride sheets were investigated by performing density functional theory calculations. The dopant atoms were substituted in a neutral charge state at either the B or the N site in the system as an impurity. All the systems under consideration were fully optimized.A systematic study was performed to see the effect of cell size on the calculated quantities, such as bond length, charge transfer, and defect formation energies. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Therefore, doping Nb at the B site is energetically preferable than at the N sites. In agreement with our results KoK¨TEN, H and co-worker [31] have reported that doping silicon (Si) in B sites are energetically more favorable than N sites of monolayer hBN. Khan et al [32] also reported from DFT formation energy calculations doping Sn at B sites of hBN requires less energy than N sites.…”
Section: Defect Formation Energy and Structural Stability Of Nb-doped...supporting
confidence: 93%
“…Therefore, doping Nb at the B site is energetically preferable than at the N sites. In agreement with our results KoK¨TEN, H and co-worker [31] have reported that doping silicon (Si) in B sites are energetically more favorable than N sites of monolayer hBN. Khan et al [32] also reported from DFT formation energy calculations doping Sn at B sites of hBN requires less energy than N sites.…”
Section: Defect Formation Energy and Structural Stability Of Nb-doped...supporting
confidence: 93%
“…The material showed enhanced H 2 and H 2 O 2 production rates and good stability, potentially due to the promotion of charge separation and inhibition of their recombination. Theoretical studies have also investigated the mechanical and electronic properties and thermodynamic stability of P-doped hBN layers, where P would replace either B or N atoms in the structure. P incorporation would cause bond lengthening and structural distortion due to inclusion of their sp 3 bonds in the otherwise sp 2 bonding system of h-BN. Especially P B defects could affect the optical properties of BN and reduce the band gap promoting visible light harvesting.…”
Section: Introductionmentioning
confidence: 99%